Os (des)caminhos da metropolização: reestruturação socioespacial na (re)produção da metrópole de Belo Horizonte - Igor Rafael Torres Santos (2011)
This study aims to make a theoretical contribution on the contemporary process of (re) production of Belo Horizonte having as a central element of analysis a restructuring socio-spatial process that we believe is rapidly developing in its North Vector Expansion. Based on the understanding of the metropolis as a whole and the socially produced space as a central element, articulator of the events in question, we seek to relate the various projects and the many infrastructural interventions that serve here as examples of both the general process of social capitalist reproduction and a more specific process, based on the feasibility or attempt to open a new axis of accumulation in the urban-metropolitan spatiality of the North Vector. Keeping in mind concepts such as historical-geographical materialism and dialectic, the uneven geographical development, and the social-economic formation, we seek to situate an analysis that does not lose sight of the contradictions present in the socio-spatial dialectics and social processes that are often forgotten (or simply left out) for some analysis that want to recognize only what appears on the surface, the appearance, and almost never its content (or essence). Featuring some public and private actors who have participated actively in this process of restructuring and socio-spatial metropolitan (re)production, this project gives greater prominence to the role played by the State of Minas Gerais in the "driving" of all these processes, showing not only the major equipments and infrastructure committed by it (the State) in the spatiality highlighted, as well as the return and (re)interest in a metropolitan planning carried out by the State and that nowadays has taken the form of a neoliberal urbanism.